Roles for Faculty in Reducing Barriers to Success for Part-Time Graduate Students - Heather L. Stuckey; Marian R Walters (Adult Education Research Conference, 2008)
There is limited research on the barriers to successful degree completion for part-time graduate students. The purpose of this paper is to present the results of a survey on former part-time graduate students at Penn State Harrisburg and to discuss the influence that faculty and advisors can have on their success in completing graduate degrees.